Implementation of the Policy on The Appointment and Dismissal of Village Apparatus at The Service of Community and Village Empowerment Pasangkayu District: Study of the Appointment and Dismissal of Bulubonggu Village Officials, Dapurang Sub-District - Nasir Mangngasing; Rachmat N.; M. Nur Alamsyah (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
This research examines the Implementation of the Policy for Appointment and Dismissal of Village Officials at the Community and Village Empowerment Service of Pasangkayu Regency by studying the Appointment and Dismissal of Village Officials in Bulubonggu, Dapurang sub-District using George C. Edward III's policy implementation model which departs from the phenomenon of post-election appointment and dismissal of Village Apparatus. Village Heads simultaneously. The research method uses a qualitative descriptive approach and determines informants using purposive sampling. The research informants were the Head of Service and staff at the Postingkayu Regency Community and Village Empowerment Service Office, the Secretary of the Dapurang District Head, the Head of Bulubonggu Village, and the Chair of the BPD of Bulubonggu Village. Data collection uses observation, interviews and documentation. Data analysis uses Miles and Huberman's interactive model approach, namely data collection, data reduction, data presentation, and conclusion verification. The research results show that: (1) The Pasangkayu Regency Government has not carried out special outreach regarding policy material for the appointment and dismissal of village officials. (2) There is no budget specifically allocated to implement the policy on appointing and dismissing Village Officials. (3) There are no Standard Operating Procedures made in the form of Regent's Regulations which serve as a reference for implementers at the Village level. Based on the dimensions of policy implementation, the George C. Edward III model is an inseparable system, so if there are still things that are not fulfilled among these systems, it can be concluded that the implementation of the policy has not been effective.